Niszczenie plakatów wyborczych: analiza prawnokarna i kryminologiczna z uwzględnieniem rozwiązań prawnych wybranych państw - Hernacka-Janikowska, Anna (Studia Prawa Publicznego, 2026)
The article discusses the destruction of election posters both from a criminal law and a criminological perspective. The analytical approach adopted in this article draws on fundamental research assumptions in this field. The author explains the most important concepts, presents the key legal regulations, and discusses the statistical dimension of the phenomenon. An important cognitive element is also the analysis of the phenomenon in a criminological context, in which the most significant criminological theories are presented, as well as the consequences associated with the phenomenon under discussion. Moreover, the author points to examples of legal solutions in selected countries, including France, Germany, the United Kingdom, and the United States. The author identifies the motivations of the perpetrators and simultaneously emphasizes that such behaviours may intensify particularly in the pre-election period, as well as due to the rising level of social and political emotions in the public sphere. Special attention should be paid to the fact that the destruction of electoral materials constitutes a significant problem not only for candidates competing for political power, but also represents a manifestation of weakening and low political culture, a lack of respect for political pluralism and the choices of others, and a serious violation of generally accepted norms of public order and law. It is also evident that misdemeanours and/or crimes involving the destruction of electoral materials generate additional costs for candidates, and that a comprehensive view of the scale of the phenomenon may also lead to the emergence of “poster wars”, in which supporters of a given political option regularly destroy their opponents’ electoral materials.